The Role of Contextual Factors in Cyberspace Harm, Anxiety, Aggression, and Students\' Academic Performance - Zahra Sadat Aghaei; Maryam Kian (Journal of Social Behavior and Community Health)
Background: Nowadays, cyberspace has presented both concerns and interests for the educational researchers. This study aimed to investigate the role of contextual factors in cyberspace harm, anxiety, aggression, and academic performance. Methods: A descriptive correlation research method was applied. The research population covered all high school students in Yazd (21,328 students). The number of 377 students were chosen as the sample through a stratified sampling based on the Cochran's formula. The research tools included the questionnaires of contextual factors, and the standard scales of cyberspace harm, anxiety, aggression, and academic performance. The validity and reliability of the scales were determined. Data were analyzed by variance, t-test, and Tukey post hoc test. Results: The findings showed that there are significant differences in cyberspace harm according to some contextual variables such as gender, educational and academic levels, educational district, type of school, field of study, and parents' occupation. More precisely, the harm of cyberspace was more high among the schools of District 2, non-public schools, and the academic field of humanities. Moreover, there was no relationship between the parents' education and the other variables. However, there was a significant relationship between the parents' occupation, regarding the employed mothers, as well as anxiety. Conclusion: In general, it can be concluded that cyberspace could provide students some challenges as it is affected by various contextual factors. According to the findings, several practical suggestions were presented in the study.